Perencanaan Pendidikan Karakter di SD Al-Irsyad Al-Islamiyyah 02 Purwokerto - Sudiro Sudiro; Sutrimo Purnomo; Juwita Fani Arizki; Margi Dwi Nastiti; Anugrah Wiranti Sukma (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Good character is the ultimate and main goal in education. Field facts show that not a few young people, even students, commit immoral acts that should not be done. This indicates that the goals of education in Indonesia have not been achieved perfectly. Various factors contributed to this failure, including weak character education planning. This study aims to analyze the planning of character education in SD Al-Irsyad Al-Islamiyyah 02 Purwokerto. This research is a type of field research that is descriptive qualitative. The results of this study indicate that the planning of character education at SD Al-Irsyad Al-Islamiyyah 02 Purwokerto is a participatory professional structural, namely character education planning that involves various parties in the educational institution starting from the level of foundation management (LPP), school management (headmaster) and vice principals), homeroom teachers/teachers to the active involvement of guardians of students with duties and responsibilities according to their respective capacities for the achievement of the goals that have been set. The stages of character education planning carried out by SD Al Irsyad Al Islamiyyah 02 Purwokerto include determining character education goals, distributing tasks and responsibilities (job descriptions, and developing character education plans.